Evaluation of the religious influence on the feeling of guilt in patients with chronic pain - a review (Research, Society and Development, 2021)
Introduction / Objective: Based on the assumption that pain can be perceived as punishment (pain = penalty), and that this concept of guilt is present in the Judeo-Christian civilization, we decided to review the literature on relevant religious and guilt - which is also a source of suffering - in the management of chronic pain. Methodology. Three searches were carried out that included all articles listed until July 2021 within the PUBMED database. MeshTerm and Boolean operators were used in the following combinations: chronic pain AND religion AND guilt NOT yoga NOT meditation; Chronic pain AND religion NOT yoga NOT meditation; chronic pain AND guilt. Results. Studies carried out in different countries point to the relevance of the chronic relationship of chronic pain to the patient, interfering in a positive way in their evolution, without, however, investigating their relationship with feelings of guilt. Conclusions. The literature is rich in articles on the influence of religiosity in coping with pain, but mentions of feelings of guilt are limited to a single article.